Пошаговое объяснение:
1)3/7 + 5/6=18/42+35/42=1 11/42
2) 11/12 - 7/8=22/24-21/24=1/24
3)5/9 : 10/27=5/9*27/10=3/2=1 1/2
4)1 8/25 * 1 4/11=33/25*15/11=9/5=1 4/5
5)5/14 * 7/30=1/12
6) 4 4/9 : 1 2/3=40/9*3/5=8/3=2 2/3
(x+2 5/6):20 + 7 1/5= 7 1/2
(x+2 5/6):20 =- 7 1/5+ 7 1/2
(x+2 5/6):20 =7 5/10-7 2/10
(x+2 5/6):20=3/10
Х+2 5/6=3/10*1/20
Х+2 5/6=3/200
Х=3/200-2 5/6
Х=9/600-2 500/600
Х=-2 491/600
4 5/9-2 5/6=4 10/18-2 15/18=1 13/18 кг
во втором ящике
4 5/9+1 13/18=4 10/18+1 13/18=5 5/18 кг в двух ящиках
Х:7=4 5/7
Х=4 5/7*7
Х=33/7*7
Х=33
ответ:
пошаговое объяснение:
1
1) (-∞; 0)∪(0; +∞)
2) (-∞; 3)∪(3; +∞)
3) (-∞; 7)∪(7; +∞)
4) (-∞; 0)∪(0; +∞)
5) (-∞; 1)∪(1; +∞)
6) (-∞; -4)∪(-4; 4)∪(4; +∞)
7) (-∞; -11)∪(-11; 2)∪(2; +∞)
2
1)=2/3
2)=b/c
3)=b/c
4)=b/y
5)=((a(a-b))/ac=(a-b)/c
6)=((a(a-b))/((a(a+b))=(a-b)/(a+c)
7)аналогично
8)аналогично
9)аналогично
10)=((x-1)(x+1))/((x(x-1))=(x+1)/x
11)=x^2/((x(x+1))=x/(x+1)
12)также как и 10
13)=1/m
14)=(a-3b)/((a-3b)(a+3b)=1/(a+3b)
15)=p
16)=так же как и 14
17)=((a-b)^2)/(a-b)=a-b
18)далее аналогично
Р=0,1*0,1*0,1=0,001